A rat model of diabetic complications induced by high-fat diet and low-dose streptoxotocin injections - Binh, Doan Viet; Kim Dung, Nguyen Thi; Nhi, Nguyen Bich; Chi, Phan Van (Academia Journal of Biology, 2013)
Diabetes can cause micro- and macrovascular complications, which contribute greatly to the morbidity and mortality associated with the disease. Animal model of diabetic complications are widely used when studying the underlying mechanisms behind diabetic complications and consequences of the disorder. In this paper presented for the first time the development of a new rat model of diabetic complications induced by high-fat diet and low-dose streptozotocin (STZ) injections. Male Wistar Rats were fed regular pellet or high fat diet (60% calories from fat). After 6 weeks, rats fed regular pellet received vehicle (controls). Rats fed with high fat diet were given once or repeated if necessary, injection of a low-dose STZ (35 mg/kg) to induce diabetes. Diabetic rats were than continuously fed with high fat diet and sacriﬁced 24 weeks after STZ injection. Blood and urine were collected for determination of biochemical parameters. Histological changes in the aorta and kidney were examined. At the end of the experiment, blood glucose, HbA1c and microalbumin showed at higher level. All of the high fat diet plus STZ injection rats exhibit remarkable lesions and plaque in their aorta representing damage to large blood vessels. However, they demonstrated features of different glomerulopathy. Rats suffered from hyperglycemia in whole studying time exhibit global glomerulosclerosis, hyaline arteriosclerosis and glomerular nodule which are comparable with characteristics observed in later stage of human nephropathy. The rest diabetic rats demonstrated features of mild nephropathy corresponding with a former stage of kidney disease.